Integrating Palliative Care into Critical Care: A Quality Improvement Study. (September 2015) - Hsu-Kim, Cynthia; Friedman, Tara; Gracely, Edward; Gasperino, James
Background: Many terminally ill patients experience an increasing intensity of medical care, an escalation frequently not consistent with their preferences. In 2009, formal palliative care consultation (PCC) was integrated into our medical intensive care unit (ICU). We hypothesized that significant differences in clinical and economic outcomes exist between ICU patients who received PCC and those who did not. Methods: We reviewed ICU admissions between July and October 2010, identified 41 patients who received PCC, and randomly selected 80 patients who did not. We measured clinical outcomes and economic variables associated with patients' ICU courses. Results: Patients in the PCC group were older (average 64 years, standard deviation [SD] 19.2 vs 55.6 years, SD 14.5; P = .021) and sicker (median Acute Physiology and Chronic Health Evaluation IV score 85.5, interquartile range [IQR] 60.5-107.5 vs 60, IQR 39.2-74.75; P < .001) than the non-PCC controls. PCC patients received significantly more total days of ICU care on average (8 days, IQR 4-15 vs 4 days, IQR 2-7; P < .001), had more ICU admissions, and were more likely to die during their ICU stay (64.3% vs 12.5%, P < .001). Median total hospital charges per patient attributable to ICU care were higher in the PCC group than in the controls (US315, 493, IQR US156, 470-US486, 740 vs US116, 934, IQR US54, 750-US288, 660; P < .001). After we adjusted for ICU length of stay, we found that median ICU charges per day per patient did not differ significantly between the groups (US37, 463, IQR US27, 429-US56, 230 vs US41, 332, IQR US30, 149-US63, 288; P = .884). Median time to PCC during the ICU stay was 7 days (IQR 2-14.5 days). Conclusions: Patients who received PCC had higher disease acuity, longer ICU lengths of stay, and higher ICU mortality than controls. "Trigger" programs in the ICU may improve utilization of PCC services, improve patient comfort, and reduce invasive, often futile end-of-life care.